1992
DOI: 10.1093/ajcp/98.4.408
|View full text |Cite
|
Sign up to set email alerts
|

p53 and c-erbB-2 Protein Expression in Breast Carcinomas: An Immunohistochemical Study Including Correlations with Receptor Status, Proliferation Markers, and Clinical Stage in Human Breast Cancer

Abstract: Receptor status, proliferative activity, loss of differentiation, inactivation of tumor suppressor genes, and overexpression of oncogenes are related events that may affect the prognosis of patients with breast cancer. Ninety-seven unselected breast carcinomas were immunostained for estrogen and progesterone receptors, Ki-67 proliferation-associated antigen, p53 tumor suppressor gene product (p53), and c-erbB-2 protein. Immunohistochemical results and clinical data were compared. Altered p53 expression (regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
36
0
10

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 0 publications
11
36
0
10
Order By: Relevance
“…These results are in keeping with the findings of previous similar studies (Cattoretti et Previous studies have shown that the presence of detectable p53 protein in breast cancer is significantly correlated with increased levels of c-erbB-2 oncoprotein (Iwaya et al, 1991;Barbareschi et al, 1992;Poller et al, 1992;Spandidos et al, 1992;Martinazzi et al, 1993), and EGFR Poller et al, 1992), but similar correlations were not observed in our material. Correlation between Rb and p53 structural abnormalities has been reported in breast carcinoma and in several other malignant tumours (Hall and Lane, 1994).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in keeping with the findings of previous similar studies (Cattoretti et Previous studies have shown that the presence of detectable p53 protein in breast cancer is significantly correlated with increased levels of c-erbB-2 oncoprotein (Iwaya et al, 1991;Barbareschi et al, 1992;Poller et al, 1992;Spandidos et al, 1992;Martinazzi et al, 1993), and EGFR Poller et al, 1992), but similar correlations were not observed in our material. Correlation between Rb and p53 structural abnormalities has been reported in breast carcinoma and in several other malignant tumours (Hall and Lane, 1994).…”
Section: Discussionsupporting
confidence: 94%
“…In the immunostaining analyses using clinical breast cancer tissues, ErbB2 protein overexpression was frequently found with p53 altered expression [32,33]. In addition, double immunohistochemical staining results showed p53 and ErbB2 immunoreactivity in the same cells [33]. Hence, it would be plausible to hypothesize that p53 function regulates the expression of ErbB2.…”
Section: Discussionmentioning
confidence: 99%
“…Diaminobenzidine was used as the peroxidase substrate and the sections were counterstained with methylgreen. Only cases exhibiting distinct membrane staining in more than 80% of Paget's cells were identified as positive for c-erbB-2 overexpression (Barbareschi et al, 1992).…”
Section: Immunohistochemistrymentioning
confidence: 99%